1994
DOI: 10.1021/jf00040a001
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol- vs Glycerol-Plasticized Whey Protein Edible Films: Integrated Oxygen Permeability and Tensile Property Evaluation

Abstract: An integrated approach for evaluation of the oxygen permeability and tensile properties of plasticized whey protein-based edible films was developed. Relative humidity had an exponential effect on the oxygen permeability of whey protein films. The increase in oxygen permeability caused by increasing concentrations of glycerol was greater than that of sorbitol. Increasing concentrations of both glycerol and sorbitol resulted in significantly decreased tensile strength and increased elongation. Sorbitol was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
323
3
31

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(405 citation statements)
references
References 4 publications
33
323
3
31
Order By: Relevance
“…The tensile strain increased with increasing level of glycerol from 1:0.25 to 1:0.5 but decreased thereafter with further increase in concentration to 1:0.75. These results are in agreement with those of McHugh and Krochta (1994a) for glycerol-plasticized WPI films. Excess plasticization increased the free volume in the film-network and weakened the intermolecular forces between adjacent polymer chains, thereby reducing TS and EM (Banker 1966).…”
Section: Thickness Of Casein and Wpc Filmssupporting
confidence: 91%
See 1 more Smart Citation
“…The tensile strain increased with increasing level of glycerol from 1:0.25 to 1:0.5 but decreased thereafter with further increase in concentration to 1:0.75. These results are in agreement with those of McHugh and Krochta (1994a) for glycerol-plasticized WPI films. Excess plasticization increased the free volume in the film-network and weakened the intermolecular forces between adjacent polymer chains, thereby reducing TS and EM (Banker 1966).…”
Section: Thickness Of Casein and Wpc Filmssupporting
confidence: 91%
“…Maynes and Krochta (1994) reported that transparent and functionally desirable edible films and coatings could be formed from components of milk protein. McHugh and Krochta (1994a) and Fairley et al (1996) developed transparent whey protein films with good oxygen, aroma and barrier properties. Pérez-Gago et al (1999) reported that native whey protein isolate (WPI) generally produced totally water-soluble films while heat-denatured solutions of WPI produce films in which the protein was insoluble.…”
Section: Introductionmentioning
confidence: 99%
“…All films with low amounts of glycerol had higher tensile strength and lower percent elongation at break, in agreement with TANADA-PALMU et al [43]. This similar behavior has been reported for other films [16,29,34]. Films with vital gluten and both concentrations of glycerol (15 and 25%) showed significantly higher percent elongation at break than the films made with gluten from Brazilian wheat flours.…”
Section: -Mechanical Propertiessupporting
confidence: 89%
“…Film formulation was prepared according to McHugh et.al [3], Perez-Gago et.al [4], Anker et al [5] and Oses et.al [6]. Aqueous solutions of 5% (w/w) WPC were prepared and heated at 90°C for 30 min.…”
Section: A Film Formation Methodsmentioning
confidence: 99%